قياس الطلب النهائي في الكويت - خليل بدوي (Dirasat in Economics and Business, 1984)
1 - Development of the final demand end its compom in Kuwait dur in the period (1970-1901). 2 - Forecast at the final demand and Its comparts at yan (1904 & J ), and this years is selected as its normal extension to the period of study, and to avoid any lag pe ried from one side, and to avoid any external factors that may affect the estimation if there is along intervals between the cel period which we study. 3- Construction of simple econometric model for the demand in Kuwait, which we can wsing the 11 The period of study (1970-1971 showed that the values of final demand are increasing, which the areal annual rate of Ince during the pe riad of study we final demand 1 )-Government final consumption expenditure (2016) - private finale penditure (19 ) arvatent (26%) - exports (29%) importa I would like to get out that they rage of anal rate of increase may not represent the annual rate of growth for the final demand and is competens tion to asit Influence of price level variation on the earrent prices, which may result that the increase is more We con obrve that the next of ex first priority between the components at the final demand during the period af study, and is lagi becse the KoWat economie depende production In To Sare the value of final de mand and its components during the period 1884- L we see the first 15 er equation final demand velcal-expects, and the second le neer equations government finale sumption expenditure-private final Ca p tion expenditure-import for the Ird during the period o This since of the parts the seat yold that all persones Lience, and the R) a large for any equation, which gives us the confidence